Short-term symptom improvement in infants with suspected cow’s milk protein allergy using amino acid formula: a prospective cohort analysis - Wilsey, Michael J.; Baran, Jessica V.; Lamos, Luke; Beacker, Jesse; Florio, Jared; Oliveros, Lea; Sriaroon, Panida; Brown, Jerry M.; Vanderhoof, Jon A. (Frontiers in Nutrition, 2023)
Background Cow’s milk protein allergy (CMPA) occurs commonly in infants. While the long-term efficacy of amino acid formulas for managing CMPA is well-established, there is limited data on the short-term symptom improvement of using amino acid formula (AAF). Objective This study aimed to determine the short-term effects of managing suspected CMPA in infants aged 6 months and under using a commercial AAF. Methods Healthcare providers who treated infants with suspected CMPA aged 6 months or younger (n = 104) provided de-identified survey data in this prospective study. Healthcare providers scored symptoms for severity from 0 to 3 (none, low, moderate, severe) before using a commercial AAF at Visit 1 and at Visit 2 (3–6 weeks later). Results Gastrointestinal (94%), skin (87%), respiratory (86%), and uncategorized symptoms (89%) improved from AAF initiation, and these findings were consistent across different follow-up visit durations. Conclusion This study is the most extensive prospective analysis conducted in the United States examining the short-term change in suspected CMPA symptoms using an AAF. These findings suggest that AAF may decrease the severity of suspected CMPA symptoms in infants 6 months or younger, often by the next follow-up visit. Further randomized controlled trials are required to confirm these initial findings.